ORGANISING A «SERATA ITALIANA»: A PROJECT-BASED LEARNING EXPERIENCE WITH FLEMISH STUDENTS OF L2 ITALIAN (ItalianoLinguadue, 2025)
This article presents the results of a qualitative study analysing the strengths and weaknesses of an innovative Project-Based Learning (PBL) approach to Italian foreign language acquisition, focused on the organisation of a cultural event. The findings are based on a 5-year pilot experience with Flemish university students enrolled in the Italian Public and Business Communication course at Ghent University (Belgium). The participating students were entrusted with the conceptualisation and execution of an Italian-themed benefit event for a non-academic audience, which required seeking support from Italian-speaking sponsors and collaborators, as well as the use of various project management tools. This case study, which examined student portfolios and a questionnaire through Thematic Analysis, demonstrates the success of the applied PBL method in terms of student motivation and creativity, project management skills (collaboration, planning, networking), self-awareness, and a specific set of communication skills. At the same time, the observed level of stress among students suggests that this PBL approach would benefit from a well-balanced focus on both language acquisition and the accomplishment of the perceived purpose, namely, a well-attended, enjoyable, and relevant event. With these considerations, this article contributes to the scholarship on PBL in foreign language acquisition.Organizzare una “Serata italiana”: un’esperienza di apprendimento basato su progetto con studenti fiamminghi di  italiano L2 Questo articolo presenta i risultati di uno studio qualitativo che analizza punti di forza e debolezze di un innovativo approccio di apprendimento basato su progetto (project based learning: PBL) per l’acquisizione dell’italiano L2, incentrato sull’organizzazione di un evento culturale. I risultati si basano su un’esperienza quinquennale con studenti universitari fiamminghi iscritti al corso di Comunicazione Pubblica e Aziendale in italiano presso l’Università di Gand (Belgio). Gli studenti partecipanti sono stati incaricati della progettazione e realizzazione di un evento benefico a tema italiano per un pubblico non accademico, compito che ha richiesto la ricerca di sostegno da parte di sponsor e collaboratori italofoni, nonché l’uso di vari strumenti di project management. Questo caso di studio, che ha esaminato i portfolio degli studenti e un questionario attraverso un’Analisi Tematica, dimostra il successo di questo metodo PBL per quanto riguarda la motivazione, la creatività e la consapevolezza di sé degli studenti, le competenze relative alla gestione di progetti (collaborazione, pianificazione, networking) e un insieme specifico di competenze comunicative. Allo stesso tempo, i livelli di stress espressi dagli studenti suggeriscono che questo approccio PBL richiede un buon equilibrio tra obiettivi di apprendimento linguistico-gestionale e finalità percepite dagli studenti, ossia la realizzazione di un evento pertinente, piacevole e ben frequentato. Con queste considerazioni, l’articolo contribuisce alla letteratura accademica sull’uso del PBL nell’acquisizione di lingue straniere.